THE CONTEMPORARY RELEVANCE OF MAHARAJA AGRASEN’S ’ONE RUPEE, ONE BRICK’ PRINCIPLE IN ADDRESSING SOCIOECONOMIC INEQUALITIES - Gupta, Deepak; Gupta, Atul; Vashistha, Sachin; Aparna; Yadav, Harish (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The primary objective of the present study is to undertake a through and critical examination of the economic principles that are intrinsically embedded within Maharaja Agrasen’s philosophical framework encapsulated in the notion of "One Rupee and One Brick," while simultaneously assessing the significance and practicality of these principles in addressing the pervasive socioeconomic inequalities that are evident in contemporary society. The paradigm articulated by the idea of "one rupee, one brick" holds paramount importance in enhancing the accessibility of educational resources for individuals who are economically marginalized and, as a consequence, find themselves deprived of the opportunity to secure educational experiences and other benefits. The theoretical construct exemplified by the principle of one rupee and one brick exhibits substantial potential for positive impact when effectively operationalized at the organizational level, particularly among numerous entities that have already adopted this innovative concept as a means to mitigate and alleviate regional disparities.